Factors predicting a change in diagnosis in patients hospitalised through the emergency room: a prospective observational study. Issue 5 (11th May 2016) - Hautz, Stefanie C; Schuler, Luca; Kämmer, Juliane E; Schauber, Stefan K; Ricklin, Meret E; Sauter, Thomas C; Maier, Volker; Birrenbach, Tanja; Exadaktylos, Aristomenis; Hautz, Wolf E
Abstract : Introduction: Emergency rooms (ERs) generally assign a preliminary diagnosis to patients, who are then hospitalised and may subsequently experience a change in their lead diagnosis (cDx). In ERs, the cDx rate varies from around 15% to more than 50%. Among the most frequent reasons for diagnostic errors are cognitive slips, which mostly result from faulty data synthesis. Furthermore, physicians have been repeatedly found to be poor self-assessors and to be overconfident in the quality of their diagnosis, which limits their ability to improve. Therefore, some of the clinically most relevant research questions concern how diagnostic decisions are made, what determines their quality and what can be done to improve them. Research that addresses these questions is, however, still rare. In particular, field studies that allow for generalising findings from controlled experimental settings are lacking. The ER, with its high throughput and its many simultaneous visits, is perfectly suited for the study of factors contributing to diagnostic error. With this study, we aim to identify factors that allow prediction of an ER's diagnostic performance. Knowledge of these factors as well as of their relative importance allows for the development of organisational, medical and educational strategies to improve the diagnostic performance of ERs. Methods and analysis: We will conduct a field study by collecting diagnostic decision data, physician confidence and a number of influencing factors in a real-world setting to model real-world diagnostic decisions and investigate the adequacy, validity and informativeness of physician confidence in these decisions. We will specifically collect data on patient, physician and encounter factors as predictors of the dependent variables. Statistical methods will include analysis of variance and a linear mixed-effects model. Ethics and dissemination: The Bern ethics committee approved the study under KEK Number 197/15. Results will be published in peer-reviewed scientific medical journals. Authorship will be determined according to ICMJE guidelines. Trial registration number: The study protocol Version 1.0 from 17 May 2015 is registered in the Inselspital Research Database Information System (IRDIS) and with the IRB ('Kantonale Ethikkomission') Bern under KEK Number 197/15.